The Repetition of the Void and the Materialist Dialectic - Kolšek, Katja (Filozofski vestnik, 2013)
The article discusses the question of the relationship between the void and repetition as the basis for the continuation of the discussion of the materialist dialectic in the light of the events of May 1968 in France and the exchange between Lacanian psychoanalysis, the Althusserian circle, and the work of Alain Badiou as regards the question of the cause of the structure. It presents the question of the minimal difference within the repetition between the lack and the hole, which according to Slavoj Žižek equals the virtual objet a as the basis of the parallactic change in the structure. On the foundation of the matrix of Badiou’s materialist dialectic as the logic of scission, it interprets the work of Althusser as a materialist dialectic repetition of the overdetermination in the aleatory encounter, which retroactively produces the third and new possibility of the continuation of the materialist dialectic.